Perceptions on 'free' tertiary education and operational budgeting within a public university - Tewe, Remilekun Felix (Vaal University of Technology, 2022)
A series of strikes by public university students protesting the exorbitant cost of tertiary education across South Africa, a country where extreme poverty is pervasive, brought the entire country to a virtual standstill in 2015 and set the stage for government to be coerced into implementing a ‘free’ tertiary education policy that it neither planned nor prepared for. The result is that, since then, universities across the country have struggled greatly to meet their financial needs. The taxation rates have being increased, and thus government must protect the monetary space to support their plans in upcoming years. This implies that any financing activated by the government to support the financial difficulties in tertiary education must be re-prioritized from other government programmes. Therefore, what should the universities’ management do to strike a harmony between budget cuts from the government as result of ‘free’ tertiary education implementation, inflationary increment of operational expenses and ‘free’ tertiary education? The primary objective of this study is to examine the perceptions of Heads of Department, and Director of directorates on ‘free’ tertiary education in relation to operational budgeting within a public university in the Gauteng province. The study embraced critical realism as its research paradigm as per a qualitative research approach, using semi-structured interviews to address the empirical objectives and a narrative literature review method to engage with the theoretical objectives of the study. The findings of the study reveal that participants welcome ‘free’ tertiary education as a system but are sceptical about its sustainability. This is because the government of South Africa failed to conduct a proper feasibility study on how to raise the funds needed to make the model work. The participants also specified that implementation of ‘free’ tertiary education in a developing economy such as South Africa will have a range of negative effects and will increase the financial burden on taxpayers. Thus, there is a need for the public university’s management studied to cultivate a sound and irrepressible monetary policy that can guarantee sustainable academic programmes and operations at the university. The study also contributed to the existing body of knowledge in the field by establishing that inevitable budget cuts by the government could lead to cost-cutting, compelling universities to reduce academic programmes offered, regardless of the significance of such programmes for national development in South Africa. The study recommends ways of generating additional income to cushion the negative effects of consistent budget reductions in subsidies to public universities as result of difficult economic conditions in the country.
M. Tech. (Department of Accountancy, Faculty of Management Sciences), Vaal University of Technology.
Keywords: ‘Free’ tertiary education; Student protests; Operational budgeting; Economic sense; Sustainability; Implementation; Policy of higher education; Dissertations, Academic -- South Africa.; Universities and colleges -- South Africa.; Student movements -- South Africa.; Universities and colleges--Finance -- South Africa.